2020
DOI: 10.3390/ijms21218286
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM as an E-selectin Ligand in Colon Cancer

Abstract: Metastasis is the main cause of death among colorectal cancer (CRC) patients. E-selectin and its carbohydrate ligands, including sialyl Lewis X (sLeX) antigen, are key players in the binding of circulating tumor cells to the endothelium, which is one of the major events leading to organ invasion. Nevertheless, the identity of the glycoprotein scaffolds presenting these glycans in CRC remains unclear. In this study, we firstly have characterized the glycoengineered cell line SW620 transfected with the fucosyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Herein, the adhesion of HepG2 to HUVEC was significantly reduced by the treatment with C20/C22 (Figure 2D). This cancer cell-vascular endothelial cell interaction can be assisted by the interactions between selectins that are expressed on the vascular endothelium and the selectin ligand presented on cancer cells [61]. Therefore, reducing the expression of selectin ligand on cancer cells can effectively prevent the binding of cancer cells to endothelium [62].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the adhesion of HepG2 to HUVEC was significantly reduced by the treatment with C20/C22 (Figure 2D). This cancer cell-vascular endothelial cell interaction can be assisted by the interactions between selectins that are expressed on the vascular endothelium and the selectin ligand presented on cancer cells [61]. Therefore, reducing the expression of selectin ligand on cancer cells can effectively prevent the binding of cancer cells to endothelium [62].…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis and univariate and multivariate Cox regression analyses showed consistent results, implicating SELE as an oncogene for CRC, as supported by other related studies. 10 Numerous studies [21][22][23] confirmed that SELE was strongly linked to the generation and invasion of CRC in small samples. Other researchers 24 detected preoperative serum E-selection and CA19-9 in 152 patients with CRC and 28 healthy volunteers, and showed that patients with higher serum expression levels of E-selection and CA19-9 had a significantly lower 5-year overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes have not been found in BRCA, but have shown that they act on the pathogenesis and development of other cancers. For example, FUT6 gene [48] has been found to be occupied an important position in the metastasis of colorectal cancer. In addition, study has shown that the expression of KIRREL2 gene [49] may cause congenital nephrotic syndrome.…”
Section: Identify the Key Biomarkers In Each Cancermentioning
confidence: 99%